2014
DOI: 10.4218/etrij.14.0113.0708
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Amplify-and-Forward Scheme for Parallel Relay Networks with Correlated Relay Noise

Abstract: This paper studies a parallel relay network where the relays employ an amplify-and-forward (AF) relaying scheme and are subjected to individual power constraints. We consider correlated effective relay noise arising from practical scenarios when the relays are exposed to common interferers. Assuming that the noise covariance and the full channel state information are available, we investigate the problem of finding the optimal AF scheme in terms of maximum end-to-end transmission rate. It is shown that the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Before we go any further, we first reformulate (9) in a more compact matrix form. It can be easily found that treating the scaling factors at the other relays as constants, the network can be regarded as a dual‐hop one [24]. Using more compact matrix formulation, the equivalent channel vector at the first hop is given by bold-italicfS,l0=][thinmathspacefS,k,kscriptLl0normalT and the channel vector at the second hop is given by bold-italicfl0,D=][thinmathspacefk,D,kscriptLl0normalT.…”
Section: Design Of Af Relaying Schemesmentioning
confidence: 99%
“…Before we go any further, we first reformulate (9) in a more compact matrix form. It can be easily found that treating the scaling factors at the other relays as constants, the network can be regarded as a dual‐hop one [24]. Using more compact matrix formulation, the equivalent channel vector at the first hop is given by bold-italicfS,l0=][thinmathspacefS,k,kscriptLl0normalT and the channel vector at the second hop is given by bold-italicfl0,D=][thinmathspacefk,D,kscriptLl0normalT.…”
Section: Design Of Af Relaying Schemesmentioning
confidence: 99%